Checklist of Copepoda associated with fishes from Brazil - Luque, José L.; Tavares, Luiz E.r. (Zootaxa, 2007)
One hundred and seventy-six determined species and 39 undetermined species of copepods associated with 179 marine and freshwater fish species from Brazil are listed, including information about the site of infection, host habitat, localities and references. Also, a host-parasite list is included herein.